The Synthesis of Polycarboxylate Dispersants Containing Benzenesulfonic Acid Groups and Their Performance in Promoting Coal Particle Dispersion - Lin Li; Zhisen Li; Shuo Yang; Chuandong Ma; Wenqi Zhang; Meng He; Xiaofang You (Molecules, 2025)
In this study, a polycarboxylate coal–water slurry dispersant (SSPA) containing benzenesulfonic acid groups was synthesized using allyl alcohol polyoxyethylene ether 500, sodium styrenesulfonate, and acrylic acid as raw materials. The effects of SSPA and a commercially available naphthalene-based dispersant (MF) on the slurry characteristics of low-rank coal were compared, and the maximum solid content of CWS prepared with SSPA reached 65.2%, which was 4% higher than that achieved with MF (61.2%). Unlike the more electronegative MF dispersant, SSPA features long polyether side chains that exert a robust steric hindrance effect, significantly enhancing coal particle dispersion. This results in a decrease in apparent viscosity and an increase in the stability of the CWS formulated with SSPA. Furthermore, adsorption experiments revealed that the adsorption kinetics of both SSPA and MF on coal conformed to the pseudo-second-order kinetic model. SSPA’s adsorption on coal particles followed the Langmuir isothermal adsorption model, and the KL value of 0.0094 for SSPA was greater than that of MF (0.0086). This indicates that SSPA has a stronger affinity for the coal surface. Overall, the superior adsorption efficacy of SSPA is attributed to the benzene ring in its nonpolar group, which facilitates steric hindrance with aromatic structures in coal. Additionally, SSPA improves slurry stability, achieving a penetration rate of 96.7%. Finally, the carboxylic acid groups in SSPA likely engage in electrostatic attraction with cations on the coal surface, enhancing adsorption.